Stable partitions for games with non-transferable utility and externalities - Karos, D (Springer Berlin Heidelberg, 2015)
I propose a model of coalitional bargaining with claims in order to find solutions for games with non-transferable utility and externalities. I show that, for each such game, payoff configurations exist which will not be renegotiated. In the ordinal game derived from these payoff configurations, a core stable partition can be found, i.e. a partition in which no group of players has an incentive to jointly change their coalitions.